Art, Politics, and Truth in Heidegger’s Anti-Semitism - Wünsch, Michaela (Stasis, 2016)
This article discusses the relation between art and politics by reference to Martin Heidegger’s essay on the “Origin of the Work of Art” (1971a). It argues that Heidegger’s Nazism and anti Semitism are not situated in his remarks on politics, but in his concept of art and technology. Alongside a reading of ideas on art and his fear of modern technology the question arises if this anti Semitism is crucial to Heidegger’s philosophy or if it is “banal” in the sense JeanLuc Nancy recently argued: banal according to Hannah Arendt’s judgment of Eichmann (Nancy 2015: 12). Banality implies for Nancy a doxa of antiSemitism that can be found not only in Heidegger’s Black Notebooks, but also in his concepts of history, technics, and modernity.